Empowering Leadership of the Heads as Perceived by the Employees and Employees’ Job satisfaction - Abun, Damianus; Lucas, Maynard O.; Magallanes, Theogenia; Encarnation, Mary Joy; Flores, Nathanael (Technium Social Sciences Journal, 2021)
The study aimed to determine the effect of empowering leadership and the job satisfaction of employees. To support the purpose, the literature was reviewed and theories were established to strengthen the title of the study. The study followed a research methodology and the research design was the descriptive assessment and correlational research design. To gather the data, validated questionnaires were and descriptive and inferential statistics were used to analyze the data. Weighted mean and Pearson r correlation was used to determine the level of different variables of empowering leadership and the correlation between empowering leadership and job satisfaction. The results indicate that empowering leadership of heads and job satisfaction of employees is not very high or high but a moderate extent and there is a significant correlation between empowering leadership and job satisfaction. Therefore, the hypothesis of the study is accepted.